2017
DOI: 10.1557/adv.2017.49
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-in vivo doped biosilica from living Thalassiosira weissflogii diatoms: investigation on Saos-2 biocompatibility

Abstract: Diatoms represent a natural source of mesoporous silica whose applications range from biomedical to photonic fields. Porous hierarchically organized micro structures, the biosilica shells called frustules, can be obtained by removal of the organic biological matter from the unicellular living algae. Diatoms frustules have been investigated as scaffold for bone tissue growth taking advantage of their nanostructured surface and of the possibility to chemically modify the biosilica. Here we report on an easy way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The presence of calcium ions in the structure of diatom frustules was confirmed by XRD and EDXS, but no specific values were provided. Similar to Leone [ 65 ], the presence of calcium ions in the culture medium in Li et al [ 62 ] did not cause any significant changes in the morphology of diatoms, and the authors indicated that the material obtained could be used as a haemostatic. Detailed data on the conditions of doping of diatomaceous biosilica with calcium ions are given in Table 4 .…”
Section: Metabolic Insertion Of Other Metals and Semimetals Ionssupporting
confidence: 54%
See 3 more Smart Citations
“…The presence of calcium ions in the structure of diatom frustules was confirmed by XRD and EDXS, but no specific values were provided. Similar to Leone [ 65 ], the presence of calcium ions in the culture medium in Li et al [ 62 ] did not cause any significant changes in the morphology of diatoms, and the authors indicated that the material obtained could be used as a haemostatic. Detailed data on the conditions of doping of diatomaceous biosilica with calcium ions are given in Table 4 .…”
Section: Metabolic Insertion Of Other Metals and Semimetals Ionssupporting
confidence: 54%
“…The works described above suggest that the concept of using the unique ability of diatom cultures to take up soluble metals and incorporate them into the structure of their frustules can also be applied to other metals, including nickel, europium, aluminum, zinc, iron, calcium, zirconium, and tin [ 19 , 63 , 64 , 65 , 66 , 67 , 69 , 70 , 71 ].…”
Section: Metabolic Insertion Of Other Metals and Semimetals Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study by our group, for example, addition of an aqueous solution of CaCl 2 to the culture medium of Thalassiosira weissflogii diatoms resulted in in vivo incorporation of Ca 2+ cations in the frustule bulk, and this functionalization is still evident by EDX and FTIR analyses on nanostructured isolated frustules after a harsh acid‐oxidative cleaning procedure with H 2 SO 4 , KMnO 4 , and H 2 O 2 . The resulting Ca 2+ ‐enriched biosilica shells were found to be a suitable mesoporous scaffold material for growth of bone cells (osteoblast‐like), disclosing applications in regenerative medicine.…”
Section: In Vivo Modification Of Biosilica Shellsmentioning
confidence: 96%